Discrimination of rare earth element geochemistry and co-occurrence in sediment from Poyang Lake, the largest freshwater lake in China. (February 2019) - Wang, Lingqing; Han, Xiaoxiao; Liang, Tao; Guo, Qingjun; Li, Jing; Dai, Lijun; Ding, Shiming
Abstract: Geochemical distribution of trace elements in sediments could reflect the impact of anthropogenic activities on environmental changes in aquatic ecosystems. In this study, rare earth elements (REEs) were used as geochemical tracers to study the environmental processes in a complex and dynamic aquatic environment. Both surface and core sediment samples were collected from Poyang Lake, the largest freshwater lake located in the middle-low region of the Yangtze River. Sediment samples were analyzed for their respective REE spatial distributions, fractionation, and co-occurrence patterns. The inner relationships and geochemistry characters of REEs were assessed by geostatistics and co-occurrence network analysis. Results indicated that total REE concentrations in the sediments from Poyang Lake ranged from 145.1 to 351.1 μg g −1, with an average concentration of 254.0 μg g −1 . Light rare earth element (LREE, La - Sm) enrichment was evident in all sediment samples, indicating the effects of river-lake interactions and the contributions from terrestrial inputs. The negative Ce and Eu anomalies were found in most sediment samples, indicating the differentiation between Ce, Eu, and other REEs in the processes of sediment transportation and deposition. Collectively, the identification of the major contamination sources of REEs in sediment, analyzed by the patterns of the co-occurrence networks and REE fractionation, revealed that the REEs in sediments from Poyang Lake originated both natural and anthropogenic sources and were disturbed by the impact of anthropogenic activities. Graphical abstract: Highlights: Accumulation and distribution of REEs in sediments from Poyang Lake were studied. Obvious fractionation between LREEs and HREEs is observed in sediments. A weak Ce and Eu anomalies were found in most of the sediments. Co-occurrence and fractionation patterns of REEs were used for source identification.